CONCEPTUAL FOUNDATIONS OF BUILDING THE POSITIONING MANAGEMENT MODEL FOR THE GENERAL EDUCATION INSTITUTION IN THE REGIONAL MARKET OF EDUCATION SERVICES - Dmytruk Zoia (International Journal of Innovative Technologies in Social Science, 2022)
The article deals with the conceptual foundations of building a positioning management model for the general education institution in the regional market of education services. Definitions of such concepts as «model» and «modeling» are considered. The article analyses the domestic and foreign scientists’ researches on the problems of pedagogical processes modeling and regulatory and legal documents that influence the solution of managerial problems in education, in particular to manage the positioning process in general education institution (hereinafter – GEI) in the market of education services. The author identifies certain contradictions between the challenges of the market economy in reforming the education and insufficient formation of managerial actions in the process of GEI positioning in the regional market of education services. The component of the positioning management model for GEI in the regional market of education services which is based on emotions and emotional values, and the factors that must be taken into account when implementing the process of positioning of GEI in the regional market of education services. The author highlighted a strong acting unique position which is formed on emotional (national-patriotic) values and allows an education organization to differentiate from competitors. According to the author it is the emotional (national-patriotic) – spiritual values of the Ukrainian patriot, the principles of Cossack pedagogy and public administration that are at the core of the modern positioning model for the GEI as an open social-public pedagogical system.